COMPARISON OF CRUDE OIL SOURCE-RELATED INDICATORS BASED ON C15-, Cl5+ AND C40+ PARAMETERS - Liliana López; Salvador Lo Mónaco-Trupiano (CT&F Ciencia, Tecnología & Futuro)
ABSTRACT. This work presents a comparative study of source-related indicators based on parameters determined in the C15-, C15+ and C40+ fractions in oil from the Barinas sub-basin, Venezuela. The objective was to determine whether the results obtained from High Temperature Gas Chromatography (HTGC-C40+) for the definition of organic facies and maturity, along with obtained by Whole-Oil Gas Chromatography (WOGC-C15+), to define maturity and secondary processes at the reservoirs are comparable with those obtained from biomarkers (GCMS-C15+). WOGC detected the presence of n-C5 to n-C9 alkanes, benzene and toluene, and the lack of these components indicates water washing. Oils from Caipe, La Victoria, Silvan, and Guafita not show biodegradation or water washing; Sinco show water washing and La Victoria and some from Guafita and Silvan oils presented evidence of evaporative fractionation. Biomarkers indicates that the oils derived from marine, algal and bacterial organic matter with variation in terrigenous organic matter input generated by a mature source rock with different lithofacies (siliciclastic-carbonatic). Based on CPI0 (C42-C46) five oils have values > 1, which is associated with marine depositional environments. However, 21 samples have , which considered typical of freshwater lacustrine environments, which differs from those determined in previous works based on biomarkers and isotopic studies.